A Randomized Controlled Trial of an Online Intervention to Improve Gluten-Free Diet Adherence in Celiac Disease - Sainsbury, K.; Mullan, Barbara; Sharpe, L. (Nature Publishing Group, 2013)
Objectives: To test the effectiveness of an interactive online intervention to improve gluten free diet adherence in adults with celiac disease. Methods: A Randomized controlled trial was conducted. A total of 189 adults with biopsy-confirmed celiac disease were recruited and randomized to receive the intervention (n=101) or to a waitlist control condition (n=88). Post-intervention data was available for 70 intervention and 64 waitlist participants. Three month follow-up data was obtained for 46/50 completers from the intervention group. The primary outcome measure was gluten-free diet adherence. Secondary outcomes were gluten-free diet knowledge, quality of life and psychological symptoms. Results: Results were based on intention-to-treat analyses. The intervention group evidenced significantly improved gluten-free diet adherence, and gluten-free diet knowledge following the treatment period relative to the waitlist control group. The change in knowledge did not contribute to the change in adherence. These improvements were maintained at 3-month’ follow-up. Conclusions: The online program was effective in improving adherence and represents a promising resource for individuals with celiac disease who are struggling to achieve or maintain adequate gluten free diet adherence.